Prostate cancer risk prediction using the novel versions of the European Randomised Study for Screening of Prostate Cancer (ERSPC) and Prostate Cancer Prevention Trial (PCPT) risk calculators: independent validation and comparison in a contemporary European cohort. (5th October 2015) - Poyet, Cédric; Nieboer, Daan; Bhindi, Bimal; Kulkarni, Girish S.; Wiederkehr, Caroline; Wettstein, Marian S.; Largo, Remo; Wild, Peter; Sulser, Tullio; Hermanns, Thomas
Abstract : Objectives: To externally validate and compare the two novel versions of the European Randomised Study for Screening of Prostate Cancer (ERSPC)‐prostate cancer risk calculator (RC) and Prostate Cancer Prevention Trial (PCPT)‐RC. Patients and Methods: All men who underwent a transrectal prostate biopsy in a European tertiary care centre between 2004 and 2012 were retrospectively identified. The probability of detecting prostate cancer and significant cancer (Gleason score ≥7) was calculated for each man using the novel versions of the ERSPC‐RC (DRE‐based version 3/4) and the PCPT‐RC (version 2.0) and compared with biopsy results. Calibration and discrimination were assessed using the calibration slope method and the area under the receiver operating characteristic curve (AUC), respectively. Additionally, decision curve analyses were performed. Results: Of 1 996 men, 483 (24%) were diagnosed with prostate cancer and 226 (11%) with significant prostate cancer. Calibration of the two RCs was comparable, although the PCPT‐RC was slightly superior in the higher risk prediction range for any and significant prostate cancer. Discrimination of the ERSPC‐ and PCPT‐RC was comparable for any prostate cancer (AUCs 0.65 vs 0.66), while the ERSPC‐RC was somewhat better for significant prostate cancer (AUCs 0.73 vs 0.70). Decision curve analyses revealed a comparable net benefit for any prostate cancer and a slightly greater net benefit for significant prostate cancer using the ERSPC‐RC. Conclusions: In our independent external validation, both updated RCs showed less optimistic performance compared with their original reports, particularly for the prediction of any prostate cancer. Risk prediction of significant prostate cancer, which is important to avoid unnecessary biopsies and reduce over‐diagnosis and overtreatment, was better for both RCs and slightly superior using the ERSPC‐RC.